Observation of two-dimensional superconductivity in an ultrathin iron–arsenic superconductor. (28th January 2021) - Zhang, Chi; Hu, Tao; Wang, Teng; Wu, Yufeng; Yu, Aobo; Chu, Jianan; Zhang, Han; Zhang, Xuefu; Xiao, Hong; Peng, Wei; Di, Zengfeng; Qiao, Shan; et al.
Abstract: Two-dimensional (2D) superconductors supply important platforms for exploring new quantum physics and high- T c superconductivity. The intrinsic superconducting properties in the 2D iron–arsenic superconductors are still unknown owing to the difficulties in the preparation of ultrathin samples. Here we report the fabrication and physical investigations of the high quality single-crystalline ultrathin films of the iron–arsenic superconductor KCa2 Fe4 As4 F2 . For the sample with the thickness of 2.6–5 nm (1–2 unit cells), a sharp superconducting transition at around 30 K (onset point) is observed. Compare with the bulk material, the ultrathin sample reveals a relatively lower T c, wider transition width, higher anisotropy, broader flux liquid region under the in-plane field, and smaller thermal activated energy with a 2D feature. Moreover, the angle dependent upper critical field follows the Tinkham model, demonstrating the two-dimensional superconductivity in ultrathin KCa2 Fe4 As4 F2 . The significant dimensionality effect observed here is markedly different from those observed in cuprate superconductors.